2017
DOI: 10.18203/2320-6012.ijrms20172475
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma- a prospective clinico epidemiological and pathological study

Abstract: Background: Basal cell carcinoma is the most common malignant tumour of the skin worldwide. The objective was to find out the age and sex incidence of basal cell carcinoma in patients attending the outpatient department of dermatology and to find out the various clinical and histopathological features of basal cell carcinoma.Methods: It was a prospective observational study carried out in a tertiary care hospital, Chennai, Tamilnadu, India. Patients with clinical diagnosis of basal cell carcinoma were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
4
4
0
Order By: Relevance
“…Descriptive analysis of low-risk single subtype BCC showed that nodular subtypes were the most prevalent (49.2%). These results are consistent with various previous studies (43-55% 12,29 ). The superficial subtypes in this study were 2.3% (previous study 5-8.12% 12,30 ) and infundibulocystic 0.1% (previous study 5% 12 ).…”
Section: Analysis Of Histological Subtypes and Variantssupporting
confidence: 94%
See 2 more Smart Citations
“…Descriptive analysis of low-risk single subtype BCC showed that nodular subtypes were the most prevalent (49.2%). These results are consistent with various previous studies (43-55% 12,29 ). The superficial subtypes in this study were 2.3% (previous study 5-8.12% 12,30 ) and infundibulocystic 0.1% (previous study 5% 12 ).…”
Section: Analysis Of Histological Subtypes and Variantssupporting
confidence: 94%
“…In this study, the proportion of patients suffering from BCC was higher in females (57.3%) with a ratio of 1.34:1. This result is in line with research in Poland and India which states that women are more exposed to BCC with a ratio of 1.3:1 11 and 2.3:1 12 , respectively.…”
Section: Case Analysis Based On Gendersupporting
confidence: 91%
See 1 more Smart Citation
“…Nodular basal cell carcinomas are the most common subtype, accounting for around 50-70% of basal cell carcinomas 16. They typically have a rolled edge, telangiectasia, and a central depression, with or without erosion or ulceration (fig 3).…”
Section: When Should You Suspect a Basal Cell Carcinoma?mentioning
confidence: 99%
“…Superficial basal cell carcinomas account for about 5% of basal cell carcinomas16 and typically present as a slow growing scaly pink patch (fig 4).…”
Section: When Should You Suspect a Basal Cell Carcinoma?mentioning
confidence: 99%